Leveraging value creation to drive the growth of B2B platforms - Anderson, Edward G.; Lopez, Jose; Parker, Geoffrey G. (Production and Operations Management, 2022)
Business platforms have become widespread in business to consumer (B2C) markets and their adoption is on the rise in the business to business (B2B) world. However, our understanding of platform adoption in B2B is less developed than for B2C. In the few cases where B2B platforms have been explicitly examined, it is often assumed that they can be understood using principles developed from the study of B2C platforms. However, the two types of platforms have important differences that often require different managerial policies to be successful. B2B supply chains are much more complex because of multiple echelons, the sophistication of their purchasing and other organizations, the competition they face, and the value of their data. The result is that, among other things, the nature of their value exchange is likely different. To address this gap, we create a novel framework. The value creation lens is grounded in theory and creates a better understanding of the dynamics of platform creation and growth by separating the platform's value into three components: (1) the standalone value of the product, such as a smartphone's ability to take pictures, (2) the value of other participants on the platform, such as the number of friends on Instagram or merchants on eBay, and (3) the value created by complementary products from third‐party providers, such as apps for a smartphone. A dynamic perspective explores the trajectory of differences in value between B2B and B2C platforms along with managerial implications.